SISTEM INSENTIF JASA LINGKUNGAN DI HUTAN LARANGAN ADAT RUMBIO KABUPATEN KAMPAR, RIAU - Insusanty, Enny; Sadjati, Emy (Fakultas Kehutanan Universitas Lancang Kuning, 2017)
The Indigenous Prohibited Forestof Rumbio provide benefits for the community in the form of non-timber forest products and environmental services in the form of water resources, but amid the increasing demand for land and economic demands put pressure on forests that threaten forest sustainability. Therefore, this study examines the factors that influence the participation of surrounding communities in conservation and environmental management activities and environmental services incentive system that can be adopted in the Indigenous Prohibited F orestof Rumbio. The method used in this research is survey method with questionnaire and in-depth interviews. Data analysis is descriptive using AHP method and multiple linear regression. This study result in that developed incentive programs for people around. The Indigenous Prohibited Forest of Rumbio in the framework of forest conservation are employment (24.17%), subsidy in second rank (20.15%) and improvement of conservation techniques in third rank (18. 90%). Factors that significantly influence the participation of respondents are education, knowledge, level of dependence on forests, customary institutions. Incentives are directed to the payment of environmental services by granting rights in the management of environmental services such as water use, non-timber forest product development, and tourism and education activities involving the community.